EFFECT OF RICE HUSK BIOCHAR ON NITROGEN UPTAKE AND GRAIN YIELD OF MAIZE IN THE GUINEA SAVANNA ZONE OF GHANA - Abukari, A.; Abunyewa, A. A.; Issifu, H. (UDS International Journal of Development, 2019)
The degradation of soils and the decrease of nutrients point to severe pressure to agriculture productivity in Africa. Soil fertility levels has declined and the amounts of nutrients required cannot support yield levels as they swiftly decline when cropping starts. The presently documented Integrated Nutrient Management (INM) methods promote the use of organic and inorganic fertilizer responses to restore nutrient depletion and sustain production.Â InÂ this connection rice husk biochar was used in a split plot experimental design with 12 treatments and replicated thrice (3) to evaluate the effect of rice husk biochar on maize (Zea mays) yield in a field experiment at Savannah Agriculture Research Institute (SARI), Nyankpala-Tamale. The results revealed that the addition of 2t and 4t/ha biochar with 90 and 60 kg N recorded significantly higher yields of grain and stover. N uptake were also significant at 2t and 4t/ha with increased N application. Additionally, the research showed that for increased productivity of maize, application of biochar must be combined with eitherintegrated nutrient managementor the suggested quantity of N fertilizers. Keywords:Â Biochar, Maize grain yield, Soil fertility, Nitrogen uptake, Pyrolysis Introduction